The Assessment of Pocket Mask Fit Among Malaysian Citizen - Muhamad Shahnizam Bin Mohd Hayati; Helmy Bin Mustafa El Bakri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
During this Covid-19 pandemic, a pocket mask is a crucial medical device that is used as a medium to perform cardiopulmonary resuscitation. One of the most important factors on determine the oxygen efficiency delivered is the proper fit of the devices themselves. To test the fit. 2 models are required to be tested which is the pocket mask and a face model. This research is purposely to investigate the 3D anthropometry data and also gaps between the devices and human face by applying the analytical approach of 3D scanning and software gap analysis. Because this research measure a high number of participants, the research become more accurate and precise. The result shows that the pocket mask surfaces mostly covered the front face only a little gap occurs and that gap can be overcome by applying the correct technique provided by the Malaysian Ministry of Health. The result obtained can be used as a reference to create a much better respirator in the future, this technique in this research also can be used as an example for future researchers to calculate any fit in any wearable devices